Influence Of Various Herbicide Mixtures On Weed Dynamics, Growth And Yield In Wheat (Triticum Aestivum L.) (Applied Biological Research, 2020)
A two-year field experiment was conducted during rabi seasons of 2016-17  and 2017-18 at Agricultural Farm of Palli Siksha Bhavana, Visva-Bharati,  Sriniketan, West Bengal (India) to assess the effects of herbicide mixtures  on weed population, weed biomass, weed control efficiency, weed index,  crop dry weight and grain yield in wheat crop. Eight herbicide treatments  along with weed-free and weedy check were evaluated in a completely randomized block design with three replications. Post-emergence  application of sulfosulfuron (25 g ha-1) + metsulfuron methyl (2 g ha-1) 30  days after seed sowing proved very effective against broad-leaved weeds and  annual grasses. The above treatment recorded significantly lower density  and biomass of weeds as compared to all other treatments. After weed-free  plot, maximum crop dry weight (514.35 g m-2) and highest grain yield (3.03  t ha-1) were obtained from sulfosulfuron + metsulfuron methyl (25 g a.i ha 1+ 2 g a.i ha-1) treated plot. All other herbicide mixtures tested also proved  very effective in controlling the weeds and increased wheat yield  significantly. The herbicide mixtures could be helpful to prevent or delay  the development of herbicide resistance in weeds and thus may reduceherbicide residues in soil.
Keywords: Herbicide; metsulfuron; sulfosulfuron; weed; wheat